(untitled) (Latakia University Journal -Engineering Sciences Series, 2019)
When Synchronous Optical Network (SONET) and Synchronous Digital Hierarchy (SDH) were developed, they were improved to transmit audio data. At the time, no one expected the tremendous growth in data traffic required by networks, especially the Internet. This research paper presents different ways of concatenating SONET and SDH signals, and different techniques for mapping packet data onto SONET/SDH connections. In order to handle data traffic efficiently. Virtual concatenation and link capacity-adjustment scheme (LCAS) significantly improves the efficiency of data transport, by grouping the synchronous payload envelopes(SPEs) and virtual containers (VCs) of SDH/SONET frames in a nonconsecutive manner to create virtual concatenation groups. While virtual concatenation provides the "right size" of SDH/SONET channels, LCAS increases the flexibility of virtual concatenation by allowing dynamic reconfiguration of virtual concatenation groups. The results demonstrate that virtual concatenation can improve bandwidth efficiency for different Ethernet data transfer rates, at10Mbps speed level, 100Mbps speed level, or 1000Mbps speed level to over 90% and the ability of (LCAS) to "reuse" the bandwidth to provide more resources and/or improved services that allow larger package bandwidth on demand. عندما تم تطوير الشبكة الضوئية المتزامنة Synchronous optical network (SONET) والهرمية الرقمية المتزامنةSynchronous Digital Hierarchy (SDH)، تم تحسينهما لنقل البيانات الصوتية.في ذلك الوقت، لم يتوقع أحد النمو الهائل في حركية مرور البيانات التي تتطلبها الشبكات، وخاصة شبكة الإنترنت.تعرض هذه الورقة البحثية،الطرائق المختلفة لتجميع(concatenating)إشارات SONET/SDH، وتقنيات التخطيط (mapping) المختلفة لبيانات الحزمة على وصلات SONET/SDH، من أجل التعامل مع حركية البيانات بشكل فعال.يُحسن كل من التجميع الافتراضي Virtual concatenationومخطط ضبط سعة الوصلةlink capacity-adjustment scheme (LCAS) كفاءة نقل البيانات بشكل ملحوظ، وذلك من خلال تجميع مغلفات الحمولة المتزامنة (SPEs) synchronous payload envelopesوالحاويات الإفتراضية لأطر SONETبطريقة غير متسلسلة من أجل تشكيل مجموعات التجميع الإفتراضيةvirtual concatenation groups (VCG).في حين يقوم التجميع الإفتراضي بتوفير أقنيةSONET"بالحجم الصحيح"، فإن LCASيزيد من مرونة التجميع الإفتراضي من خلال السماح بإعادة التكوين الديناميكي لمجموعات التجميع الإفتراضي.توضح النتائج، أن التجميع الإفتراضي يمكن أن يحسن كفاءة عرض الحزمة لمعدلات نقل بيانات الإيثرنت المختلفة، بمستوى سرعة 10Mbps، مستوى سرعة 100Mbps، مستوى سرعة 1000Mbps إلى أكثر من 90%.وقدرة LCAS على "إعادة استخدام" عرض حزمة لتوليد المزيد من الموارد، و/أو تقديم خدمات محسّنة تتيح إرسال عرض حزمة أعلى في أوقات الحاجة.